Martin's mice - King-Smith, Dick.; Alborough, Jez (New York : A.A. Knopf, 1998)
A farm cat who doesn't want to catch mice keeps a family of them as pets in the barn; but then he is given away to a townswoman and acquires a new perspective.
"Ages 8-12"--P. [4] of cover.
Keywords: Cats$1 (BJuvenile fictions; Cats -- Fiction; Mice -- Fiction